Existence and approximation of solutions to nonlinear hybrid ordinary differential equations. (January 2015) - Pathak, Hemant Kumar; Rodríguez-López, Rosana
Abstract: In this note, we consider the initial value problem for first order nonlinear hybrid ordinary differential equations and we discuss the existence and approximation of the solutions. The main results are related to a recent work by Dhage et al. (2014) through the restructuring of some of the hypotheses imposed and the extension of some of the results there. In addition, we provide an example to illustrate the applicability of the abstract results developed.